Critical perspectives on open development : empirical interrogati on of theory construction - Chib, Arul; Bentley, Caitlin M.; Smith, Matthew L. (Cambridge, Massachusetts : The MIT Press, 2020)
"Explores whether, for whom, and under what circumstances the free, networked, public sharing of ICT resources contributes to positive soci al change"--
Includes bibliographical references and index.
Keywords: Information technology -- Economic aspects; Information technology -- Social aspects; Information society; Information commons; Open source software; Economic development